Penerapan Model Pembelajaran Kooperatif Tipe Make A Match dalam Meningkatkan Keaktifan Siswa pada Mata Pelajaran Ips Kelas VIII di SMPN 3 Kalidawir Tulungagung - Galuh Sabila; Jani Jani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The results of this study show that: 1) The steps of implementing the make a match type cooperative learning model have several stages that must be prepared by teachers so that the learning process is taught in a structured manner, namely designing teaching modules and learning themes, preparing cards containing questions and answers, making learning assignment planning strategies, carrying out preparation and implementation of activities, couple verification, evaluation, awarding/appreciation. 2) The results in the implementation of the make a match type cooperative learning model explain that there is an increase in student learning activity and learning outcomes before and after learning. 3) Factors that affect the learning process There are supporting factors, namely student motivation and enthusiasm that encourage active involvement in the learning process, while inhibiting factors, namely the classroom atmosphere becomes unconducive during learning.